Serous retinal detachment secondary to an unsuccessful transarterial embolization in a post-traumatic carotid-cavernous sinus fistula patient: A case report - Lee, Chia-Yi; Lee, Wan-Ju Annabelle (Frontiers in Medicine, 2022)
A carotid-cavernous sinus fistula (CCF) is an abnormal communication between the cavernous sinus and the carotid arterial system. Direct CCFs arise from a direct connection between the cavernous sinus and the cavernous portion of the internal carotid artery. Nowadays, endovascular neurosurgery has become the first-line treatment modality for direct CCFs owing to the high complete obliteration rate. However, reversal of the clinical symptoms may not always be congruous after the endovascular intervention. Herein, we present a 50-year-old patient who manifested diplopia, ophthalmoplegia, and orbital congestion after a traffic accident. He had suffered head injury with right side frontal intracranial hemorrhage one month before the ophthalmic presentation. He came to our department primarily because of declining vision and for the above symptoms, and was diagnosed with direct type CCF, for which he received transarterial coil embolization. Unexpectedly, he later presented with serous retinal detachment accompanied by ocular ischemic syndrome secondary to recurrent CCF one month after the intervention, so repeat coil embolization was performed.